"Pragmatic Dimensions of Religious Discourse in Light of Its Linguistic Mechanisms and Epistemic Foundations" - salim.hmrit, salim.hmrit (El Omda in Linguistics and Discourse Analysis, 2018)
Religious discourse presupposes the presence of interlocutors: a sender and a receiver. The conditions of producing religious discourse generally align with prior knowledge, serving as a solid foundation for it as an intellectual process with an active, interactive dynamic. Religious discourse aims to highlight the qualities underlying language as a system for conveying intentions beyond the words themselves. In Western thought, religious discourse is seen as a complex weave of interlaced threads, whereas in the Arab tradition, it is understood as clarification and exposition—concerned with the matter at hand and the intention behind it. This is followed by the elements that constitute the interpretive discourse process, drawing on modern sciences, which also employ contemporary methodologies to decode the signals of religious discourse through textual analysis in order to achieve the intended purpose.